2012
DOI: 10.1007/s00285-012-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in a seasonally perturbed SIR model: avian influenza in a seabird colony as a paradigm

Abstract: Seasonality is a complex force in nature that affects multiple processes in wild animal populations. In particular, seasonal variations in demographic processes may considerably affect the persistence of a pathogen in these populations. Furthermore, it has been long observed in computer simulations that under seasonal perturbations, a host-pathogen system can exhibit complex dynamics, including the transition to chaos, as the magnitude of the seasonal perturbation increases. In this paper, we develop a seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
0
16
1
Order By: Relevance
“…Also, our results indicate several regions of (apparently) chaotic behaviour, due to the many period-doubling bifurcation curves which can give rise to period-doubling cascades (Aron and Schwartz, 1984). This multitude of period-doubling cascades is not readily observed in other seasonal systems (O'Regan et al, 2013;Rinaldi et al, 1993). Our study also shows that period-halving can occur, which has not been reported in previous studies of seasonally forced models.…”
Section: Discussioncontrasting
confidence: 59%
“…Also, our results indicate several regions of (apparently) chaotic behaviour, due to the many period-doubling bifurcation curves which can give rise to period-doubling cascades (Aron and Schwartz, 1984). This multitude of period-doubling cascades is not readily observed in other seasonal systems (O'Regan et al, 2013;Rinaldi et al, 1993). Our study also shows that period-halving can occur, which has not been reported in previous studies of seasonally forced models.…”
Section: Discussioncontrasting
confidence: 59%
“…In this section, we describe the four models that are considered in this work. The details of these models and their respective derivation assumptions can be found in [11], [13], [25] and [34].…”
Section: Selected Modelsmentioning
confidence: 99%
“…There are observations, for example in childhood diseases or avian influenza, that do not show damped characteristics rather (ir)regular cycles instead. This phenomenon can be linked to seasonal variation in contact rate b(t) or in recruitment rate g 19 . It has already been noticed that in case of periodic forcing, b 0 (t) = b 0 =const.…”
Section: Standard Epidemic Modelmentioning
confidence: 99%
“…Sufficiently large seasonal forcing or different mixing rates between sub-populations can cause large oscillations and also period doubling cascades [12][13][14][15][16][17][18] . It has also been demonstrated that for certain values of system parameters the nonautonomous models of recurrent epidemics (measles, mumps, rubella, H5N1 avian influenza) show chaotic behavior 6,[19][20][21] . Traditional SIR-like epidemic models are dissipative nonlinear low-dimensional systems with constant, periodic, quasiperiodic 22 , or term-time 3,23 external forcing whose dynamics a) Electronic mail: tkovacs@general.elte.hu is governed by (chaotic) attractors in phase space.…”
Section: Introductionmentioning
confidence: 99%